2023
DOI: 10.1080/20523211.2023.2285957
|View full text |Cite
|
Sign up to set email alerts
|

Insights into participation in ward rounds in hospitals: A survey of clinical pharmacists' perceptions

Najmaddin A. H. Hatem,
Seena A. Yousuf,
Mohamed Izham Mohamed Ibrahim
et al.

Abstract: Introduction Clinical pharmacists’ participation in ward rounds (WRs) has been a great chance to contribute to team-based care in the hospital setting and significantly improve patient outcomes and quality of life. Hence, the objective of this investigation was to explore the perceptions of clinical pharmacists in Yemen regarding their participation in WRs and the factors influencing their involvement. Methods An online survey of Yemeni clinical pharmacists was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…This observation can be attributed to the broader clinical competencies, duties, and exposure to case studies that hospital pharmacists typically possess. In addition, hospital pharmacists provide more support to physicians and have access to comprehensive patient medical profiles, which further reinforces the value they see in MTM [29]. In addition medical information in Yemen is primarily accessible in hospitals, community pharmacies lack easy access to patient medical profiles.…”
Section: Plos Onementioning
confidence: 84%
See 3 more Smart Citations
“…This observation can be attributed to the broader clinical competencies, duties, and exposure to case studies that hospital pharmacists typically possess. In addition, hospital pharmacists provide more support to physicians and have access to comprehensive patient medical profiles, which further reinforces the value they see in MTM [29]. In addition medical information in Yemen is primarily accessible in hospitals, community pharmacies lack easy access to patient medical profiles.…”
Section: Plos Onementioning
confidence: 84%
“…Furthermore, pharmacists with (1-5) years of experience well-recognized the two statements describing the primary goals of delivering MTM services. One possible explanation for these findings is Yemeni pharmacy education's current shift to a more patient-oriented curriculum, with many universities in recent years beginning to provide more courses that state the new patient-oriented roles, as well as adopting clinical pharmacy education [29,30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2011, Hodeidah University became the first university to offer a clinical pharmacy program, and in 2013, it established the first independent college of clinical pharmacy. 9,10 Previous research has indicated that there are some variations in how doctors see various types of CPSs [11][12][13][14][15][16][17][18][19][20][21] and that doctors seem to have an improved perception of CPSs if they interact with pharmacists more often. 11,[15][16][17][18][19] Doctors in Sweden are skeptical of the expertise and understanding of clinical pharmacists.…”
Section: Introductionmentioning
confidence: 99%